Computational complexity and statistical physics - Percus, Allon; Istrate, Gabriel; Moore, Cristopher (Proceedings volume in the Santa Fe Institute studies in the sciences of complexity., 2006)
Computer science and physics have been closely linked since the birth of modern computing. In recent years, an interdisciplinary area has blossomed at the junction of these fields, connecting insights from statistical physics with basic computational challenges. Researchers have successfully applied techniques from the study of phase transitions to analyze NP-complete problems such as satisfiability and graph coloring. This is leading to a new understanding of the structure of these problems, and of how algorithms perform on them. Computational Complexity and Statistical Physics will serve as.